Dampak Covid-19 di Kampoeng Heritage Malang - Yuliana Trisna Manding; Nanny Roedjinandari; Aprilia Rachmadian; Irwan Yulianto (Jurnal Perhotelan, Destinasi Wisata, Perjalanan Wisata (Jurnal Tesla), 2022)
ABSTRACT In this paper, the author pays special attention to a theme,namely the impact of covid-19 in the  Village of Heritage Malang. The problem studied in this paper is the decline in income in Heritage Village,Malang due to covid-19. The method used in this paper is a qualitative method. The purpose of this study was to determine the development of tourism in the Heritage Kajoetangan Village in the face of the covid-19 pandemic and to know the history and atmosphere of Heritage Village before and after the covid-19 pandemic. Covid-19 certainly has a big impact on tourism life. Tourism is one sector that has an important role in a city or region. Tourism can contribute the largest foregin exchange and provide employment opportunities for the local community so as to help increase tourism in the Heritage Kajoetangan Village Malang City. At the beginning of 2020, Indonesia was shaken by a very dangerous corona virus outbreak. 2020 will be a different year for all sectors, especially for the tourism sector in Heritage KajoetanganVillage,Malang city. Malang city is one of the highest increase in positive cases of covid-19. With the increase in positive cases of covid-19 in the city of malang. The government has firmly issued a policy of lockdown and limiting activities and following health protocols such as maintaining distance, wearing mask, and wasing hands. Thus the tourism sector experienced a decline in income. The results of this study show that with the corona virus all tourism places, especially in the Heritage Kajoetangan Village, Malang city, are temporarily closed. During the covid-19 pandemic, in Heritage Kajoetangan Village, Malang city did not receive touri st visits but continued to promote through social media to increase the attractiveness of future tourists.